Estudo CFD-DEM de um leito de jorro operando nos regimes denso, de transição e jet spouted bed - Almeida, Natalia Pazin (2020)
The spouted bed has been widely used in industrial processes, due to the high contact reached between particles and fluid. There are some limitations to the use of the dense spouted bed. In this conventional regime, the long residence time has a disadvantageous effect on thermosensitive materials, for example, and may cause bed blockage in operations with sticky materials, as a consequence of the low particle circulation rate. An option to avoid these fluid dynamics problems is to operate a diluted-phase spouted bed, the jet spouted bed. Numerical modeling, especially the CFD-DEM, facilitates the analysis of the flow of particles inside multiphase equipment, making it possible to obtain specific information about the solids. In this work, the dynamic of glass spheres in a Plexiglas spouted bed was studied by the CFD-DEM technique in the conventional and jet spouting, besides in the transition regime between them. The upward and downward particle velocities, as well as the local bed voidages, were analyzed, with the expansion of the inlet air velocity, besides the variation in the number of contacts, number of collisions, and the intensity of collisions inside the equipment. Experimental data from the literature were used to validate the numerical simulations. The simulations' results were satisfactory to predict the behavior of particle velocities and bed voidage. With the inlet air velocity expansion, there was an increase in the upward velocities at the spouting region and the radial distribution of voidage. Also, there was a decrease in the number of contacts and collisions between particles, as the solids are distributed along the bed. The intensity of particle collisions, however, increases with the inlet air velocity expansion. In the jet spouted bed, especially, it was observed that the local bed voidage remained close to 0.9 in all the radial positions. Besides, in this diluted regime, a higher particle collision/contact ratio was observed throughout the equipment, which makes interesting to study the jet spouted bed in operations in which the collisions between particles are more important than the slip, such as mechanical extraction. It was also observed that the steady-state takes longer to reach the diluted regime.